Mitigating the Default? The Influence of Ingroup Diversity on Outgroup Trust. Issue 1 (4th August 2021) - Winter, Kevin; Sassenberg, Kai
Maintaining social cohesion in times of increasing diversity is a major challenge of modern societies. Mitigating defaults in group-based trust could be a solution because they are often driven by stereotypes and ingroup favoritism. Ingroup diversity could be a means to achieve such a mitigation given that it increases cognitive flexibility and cognitive flexibility changes defaults in trust – in the sense of increasing low and reducing high trust. We tested whether representing one's ingroup as high (compared to low) in diversity mitigates defaults in group-based trust using a variety of well-established manipulations of ingroup diversity and measures of trust. None of the four well-powered studies (total N = 885), we conducted provided support for our hypothesis. However, an internal meta-analysis revealed a significant but very small effect in support of our prediction ( r = 0.07, 95% CI [0.01, 0.14]). Thus, a diverse representation of the ingroup asserts a mitigating impact on group-based trust, but the size of the effect is very small. Thus, real world interventions should not rely on the current effect.